Molecular characterization and drug susceptibility of isolates from MDR-TB patients in the Eastern Cape and North West provinces of South Africa - Mphahlele, Matsie Theodora (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.